Intepretasi dan Implikasi MBKM Terhadap Pengembangan Kurikulum Program Studi Pendidikan Agama Islam UII - Moh. Mizan Habibi (EL-TARBAWI, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) is government policy to enrich different learning experiences and practical skills. However, this new policy is subject to be interpreted and adapted into established existing curriculum. The aim of the research is to identify and analyze the interpretation and implications of MBKM policy in developing the curriculum of the Islamic Religious Education Study Program. Content analysis is used and reinforced by interview data. It is shown that the Islamic Religious Education study program interprets the MBKM policy as an effort to expand sources and learning media, as well as enrich perspectives in the learning process. The implication is developing the curriculum through expanding learning programs based on teaching assistance, research, community service, and edupreneurship initiatives, as well as facilitating students in the independent campus program. Â